Anti-Inflammatory Properties of Bellevalia saviczii Root Extract and Its Isolated Homoisoflavonoid (Dracol) Are Mediated by Modification on Calcium Signaling - Monica Savio; Mohammed Farhad Ibrahim; Chiara Scarlata; Matteo Orgiu; Giuseppe Accardo; Abdullah Shakur Sardar; Francesco Moccia; Lucia Anna Stivala; Gloria Brusotti (Molecules, 2019)
Bellevalia saviczii is a medicinal plant used as anti-rheumatic and anti-inflammatory herbal remedy in Iraqi-Kurdistan. The aim of this study was to evaluate the anti-inflammatory activity of its extract and the isolated homoisoflavonoid (Dracol) by studying the Ca2+-dependent NF-kB pathway. Nuclear translocation of p65 NF-kB subunit, as parameter of NF-kB activation, was visualized in human leukemic monocytes by immunofluorescence and Western blot analyses, after cell treatment with B. saviczii root extract or Dracol followed by Lipopolysaccharide stimulation. In parallel, Ca2+ signals responsible for NF-kB activation and levels of inflammatory cytokines were investigated. LPS-induced p65 translocation was evident in monocytes and both treatments, in particular that with Dracol, were able to counteract this activation. Intracellular Ca2+ oscillations were halted and the cytokine release reduced. These results confirm the traditional anti-inflammatory efficacy of B. saviczii and identify one of the molecules in the extract which appears to be responsible of this action.